Alveolar osseous defect in rat for cell therapy. Preliminary report - Raposo-Amaral, Cassio Eduardo; Kobayashi, Gerson Shigeru; Almeida, Ana Beatriz; Bueno, Daniela F.; De Souza E Freitas, Fatima Rodrigues; Vulcano, Luiz Carlos; Passos-Bueno, Maria Rita; Alonso, Nivaldo (FapUNIFESP (SciELO), 2010)
Purpose: To study were to reproduce an alveolar bone defect model in Wistar rats to be used for testing the efficacy of stem cell therapies. Additionally, we also aimed to determine the osteogenesis process of this osseous defect in the 1 month period post-surgery. Methods: The animals were randomly divided into two groups of 7 animals each. A gingivobuccal incision was made, and a bone defect of 28 mm 2 of area was performed in the alveolar region. Animals were killed at 2 weeks after surgery (n=7) and 4 weeks after surgery (n=7). Results: The average area of the alveolar defect at time point of 2 weeks was 22.27 ± 1.31 mm 2 and the average area of alveolar defect at time point of 4 weeks was 9.03 ± 1.17 mm 2. The average amount of bone formation at time point of 2 weeks was 5.73 ± 1.31 mm 2 and the average amount of bone formation at time point of 4 weeks was 19 ± 1.17 mm 2. Statistically significant differences between the amount of bone formation at 2 weeks and 4 weeks after surgery were seen (p=0.003).Conclusion: The highest rate of ossification occurred mostly from 2 to 4 weeks after surgery. This observation suggests that 4 weeks after the bone defect creation should be a satisfactory timing to assess the potential of bone inductive stem cells to accelerate bone regeneration in Wistar rats.
Keywords: Alveolar bone loss; Rats; Tissue therapy